Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4049/jimmunol.1103579
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation during Pregnancy Protects against Lipopolysaccharide-Induced Fetal Growth Restriction and Demise through Its Anti-inflammatory Effect

Abstract: LPS is associated with adverse developmental outcomes, including preterm delivery, fetal death, teratogenicity, and intrauterine growth restriction (IUGR). Previous reports showed that zinc protected against LPS-induced teratogenicity. In the current study, we investigated the effects of zinc supplementation during pregnancy on LPS-induced preterm delivery, fetal death and IUGR. All pregnant mice except controls were i.p. injected with LPS (75 μg/kg) daily from gestational day (GD) 15 to GD17. Some pregnant mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 48 publications
3
40
1
Order By: Relevance
“…Maternal LPS exposure during the second trimester caused fetal death and preterm delivery [8]. We and others found that maternal LPS exposure during the third trimester led to fetal death, fetal growth restriction, skeletal development retardation, and preterm labor [9][13]. Several studies including ours showed that maternal LPS exposure resulted in fetal teratogenesis in rats [14], mice [15], [16], and golden hamsters [17].…”
Section: Introductionmentioning
confidence: 79%
“…Maternal LPS exposure during the second trimester caused fetal death and preterm delivery [8]. We and others found that maternal LPS exposure during the third trimester led to fetal death, fetal growth restriction, skeletal development retardation, and preterm labor [9][13]. Several studies including ours showed that maternal LPS exposure resulted in fetal teratogenesis in rats [14], mice [15], [16], and golden hamsters [17].…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, developmental delay and embryo death in dairy cows at early gestation stages are the consequences of zinc deficiency and disorders of its metabolism in the organism. Experiment in vivo (19) showed that additional introduction of zinc to animals effectively protected them from lipopolysaccharide-induced intrauterine growth restriction and embryo and fetus death.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Recent studies showed that ZnSO 4 supplementation during pregnancy protects against LPS-induced fetal growth restriction and demise through its anti-inflammatory effect. [28] Nevertheless, the molecular mechanism of zinc-mediated protection against LPS induced developmental toxicity remains elusive. Present study was designed to investigate the gender biased effects of LPS injection during d14-17 of pregnancy on the neurobehavioral, biochemical and histopathological parameters in off-springs.…”
Section: +mentioning
confidence: 99%
“…[27] Increasing evidence demonstrates that zinc has an anti-inflammatory effect. [28] A recent study found that subcutaneous injection with zinc sulfate alleviated LPSinduced neurodevelopmental damage in fetal brain. [29,30] Zinc is capable of inhibiting LPS or IL-1β-induced nitric oxide (NO) formation as well as NO formation by NO synthase (NOS).…”
Section: Introductionmentioning
confidence: 99%